2022
DOI: 10.3389/fvets.2022.860771
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous L-carnitine Administration Ameliorates the Adverse Effects of Heat Stress on Testicular Hemodynamics, Echotexture, and Total Antioxidant Capacity in Rams

Abstract: Heat stress (HS) diminishes the testicular antioxidant defense systems, which adversely affect the testicular blood perfusion. Improving the testicular hemodynamics during HS conditions is of a great impact on the whole reproductive performance in rams. This study aimed to evaluate the ameliorative effects of L-carnitine (LC) on the testicular blood flow and echotextures and also on the total antioxidants (TAC) and nitric oxide (NO) concentrations in the serum during HS conditions in rams. Testicular blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
(79 reference statements)
2
12
0
Order By: Relevance
“…Therefore, higher TBF explains the lower TE values, whereas, the higher sperm cell concentration in the last three weeks of the experiment may interpret the elevated TE values. These outcomes support the concept that TE is affected by testicular dynamics either in blood flow or spermatogenesis and is useful as an indicator in the breeding soundness evaluation of male animals (El-Sherbiny et al 2022e ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, higher TBF explains the lower TE values, whereas, the higher sperm cell concentration in the last three weeks of the experiment may interpret the elevated TE values. These outcomes support the concept that TE is affected by testicular dynamics either in blood flow or spermatogenesis and is useful as an indicator in the breeding soundness evaluation of male animals (El-Sherbiny et al 2022e ).…”
Section: Discussionsupporting
confidence: 80%
“…Environmental heat stress deteriorates animal productivity and fertility potential (El-Sherbiny et al 2022b ). Since oxidative stress is the main pathway through which HS exerts its destructive impacts on male reproductive functions, numerous studies have reported that dietary supplementation of antioxidants could ameliorate HS-induced male infertility (Elokil et al 2019 ; Sharideh et al 2020 ; El-Sherbiny et al 2022c ; Fadl et al 2022c ). Mitochondria is the site where free radicals are extensively generated and induce an OS cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the reproductive system, especially scrotal ultrasonography is very important to monitor the breeding potentials and diagnose various testicular affections. Recent advances in Doppler applications have enabled researchers and veterinarians to properly assess the structural and functional aspects of the testis (Araujo and Ginther 2009;Samir et al 2021;El-Sherbiny et al 2022a, 2022b. Doppler ultrasonography is a good diagnostic method that provides both anatomical and velocimetric information on blood perfusion to the testis.…”
Section: Introductionmentioning
confidence: 99%
“…This data is significant in improving male dog productivity and reproductive pattern [52]. The improvement of testicular blood flow by the melatonin injection led to a mark in both Doppler indices parameters of the distal supra testicular arteries (PI and RI), which have a strong negative correlation with blood velocities parameters (PSV and EDV), testicular volume and intra-testicular colored areas [53][54][55]. The marked linear decline in both two Doppler indices leads to a substantial decrease in the blood flow resistance pattern and, therefore, an elevation of the testicular blood supply with an increase in sufficient nutrients and oxygen within both testes [56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%